Measuring Consumer Willingness to Pay to Reduce Health Risks of Contracting Dengue Fever - Lin, Cheng-Te (Int J Environ Res Public Health, 2020)
Located in the subtropics, Taiwan is one of the major epidemic areas for dengue fever, with severe epidemics occurring in recent years. Dengue fever has become a serious health threat to Taiwan’s residents and a potentially serious economic cost to society. This study recruited 730 random participants and adopted the contingent valuation method to understand the factors influencing the populace’s willingness to pay (WTP) to reduce the health risk of dengue fever. The results show that high-income women with children and people with higher preventive perceptions and behavior are more willing to invest in preventive measures against dengue fever. In the evaluation of WTP for preventive treatment for health risks, each person was willing to pay on average NT$751 annually to lower psychological health risks, NT$793 annually to lower the risk of illness, and NT$1086 annually to lower the risk of death.